Peabody Developmental Motor Scales-2: The Use of Rasch Analysis to Examine the Model Unidimensionality, Motor Function, and Item Difficulty - Valentini, Nadia Cristina; Zanella, Larissa Wagner (Frontiers in Pediatrics, 2022)
The Peabody Developmental Motor Scales - Second Edition (PDMS-2) is a valid and reliable instrument used in several countries, including Brazil, to assess motor skills, and identify motor deficits and eligibility for intervention for children with and without disabilities. However, the analysis of PDMS-2 items regarding the unidimensionality of the model, order of item difficulty, and whether the items portray the children's developmental trajectories still lacks investigation. Therefore, this study aims to: (1) analyze the unidimensionality of PDMS-2, (2) verify the model's capacity to explain the variance in the motor function responses, and (3) identify the level of difficulty of the items for Brazilian children. Children (n = 637; 51% girls) newborn to 71 months (M age = 21.7, SD = 18.6) were assessed using the PDMS-2. The Rasch analysis was conducted, the indexes of infit and outfit, and the point-biserial correlations coefficient were analyzed. The model unidimensionality was investigated using percentages of variance in the Rasch model (40% of variance). Results indicated that, (1) reflexes subscale, 62.5% of the items had correlations with the factor above .60; two items had inappropriate values; (2) stationary subscale, 83.3 % of the correlations of the items with the factor were above .50; one item had inappropriate values; (3) locomotion subscale, 80.0% of the correlation of the items with the factor were above .50; all items had adequate infit and outfit; (4) object manipulation subscale, 79.9% of the correlation of the items with the factor were above .50; one item had inappropriate values; (5) grasping subscale, 92.3% of the correlation of the items with the factor were above .50; one item had inappropriate values; (6) the visual-motor integration subscale, 73.6% of the correlation of the items with the factor were above .50;six items had inappropriate values. The items with unadjusted fit were removed for further analysis. No changes in reliability and separation of items and people scores were observed without the unadjusted items; therefore, all items were maintained. A unidimensional model was found, and the reliability and discriminant capability of the items were adequate, and all items should be used to assess children.